Use of a thermal camera to aid in capturing northern bobwhite quail chicks - Alicia K. Andes; Byron R. Buckley; Thomas L. Warren; Paul C. Woods; Sean R. Yancey; C. Brad Dabbert (Wildlife Society Bulletin)
Abstract There is a paucity of information concerning northern bobwhite (Colinus virginianus) chick demography caused by a deficiency of efficient published capture techniques and permanent unique markers for identification. In order to facilitate chick research, we employed a thermal camera to detect and capture chicks during the preflight stage (≤14 days old) brooded by a radiomarked female. We released a known number of chicks into native vegetation within a flight pen to test this technique. Observers (unaware of the number) then used a thermal camera to successfully count (≥95% intra‐class correlation coeff.; complete counts for each age class) and capture the chicks. In separate field tests, we homed to within 10 m of the roost location of wild radiomarked females before sunrise, circled the area until the brood heat signature was observed, and flushed the female from the chicks. We located 116 chicks from 43 broods with the thermal camera throughout the 2011 nesting season with 81% complete, 12% partial, and 7% failed captures attempts. Detection of chicks by the thermal camera was not affected by age. Complete brood abandonment was not detected as a result of capture events. The employment of a thermal camera to capture chicks should advance the success and efficiency of capture and thus promote research concerning brood ecology. © 2012 The Wildlife Society.